Bioapplications of renal-clearable luminescent metal nanoparticles. (9th May 2017) - Gong, Lingshan; Wang, Yaping; Liu, Jinbin
Abstract : This review summarizes the recent synthetic strategies of the renal-clearable luminescent metal nanoparticles, and discusses the biological behaviors and current disease-related applications of this type of biomaterials in tumor targeting, kidney disease and antimicrobial investigations. Abstract : Renal-clearable inorganic nanoparticles (NPs) that hold great potential in the future clinic translations are considered as the next generation of nanomedicine. In the past decade, enormous efforts have been dedicated to the development of renal-clearable NPs with fascinating optical properties, selective disease-targeting capabilities and low nanotoxicities. A further understanding of the design of renal-clearable luminescent metal NPs and their metabolic behavior in the body is important to achieve their clinical transition and extend their bioapplications in disease theranostics. In this review, we discuss the recent synthetic strategies of renal-clearable metal NPs in terms of the considerations of size and composition, surface chemistry and emission wavelength. We also summarize the current disease-related applications of these renal-clearable luminescent metal NPs in tumor targeting, kidney disease and antimicrobial investigations after a discussion of their biological behavior including the pharmacokinetics and biodistribution. Finally, we provide perspectives on the current challenges and upcoming chances for renal-clearable luminescent metal NPs.